Physiologic and Pathologic Angiogenesis Signaling Mechanisms and Targeted Therapy - Simionescu, Dan; Simionescu, Agneta (IntechOpen, 2017)
The purpose of this book is to highlight novel advances in the field and to incentivize scientists from a variety of fields to pursue angiogenesis as a research avenue. Blood vessel formation and maturation to capillaries, arteries, or veins is a fascinating area which can appeal to multiple scientists, students, and professors alike. Angiogenesis is relevant to medicine, engineering, pharmacology, and pathology and to the many patients suffering from blood vessel diseases and cancer, among others. We are hoping that this book will become a source of inspiration and novel ideas for all.